Uji Aktivitas Antioksidan Ekstrak Etil Asetat Daun Belimbing Wuluh (Aveerrhoa bilimbi L.) dengan Metode DPPH - Ika Fatmawati S; Haeruddin; Wa Ode Mulyana (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
A study "Test Antioxidant Activity of Ethyl Acetate Extract of startfruit Leaves (Averrhoa bilimbi L.) with the DPPH Method" with the aim is to determine the types of identified secondary metabolites identified in the ethyl acetate extract of starfruit leaves, and to determine the antioxidant activity of the ethyl acetate extract of starfruit leaves wuluh. Wuluh starfruit leaves used as much as 250 grams which were macerated with technical ethyl acetate solvent and obtained a thick ethyl acetate extract of 12.62%. The group of secondary metabolites was determined by the phytochemical method, and the method used to determine the antioxidant activity was the DPPH method. The ethyl acetate extract of belimbing wuluh leaves contains alkaloids, steroids, tannins and has a very low antioxidant activity with an IC50 value of 547.56 ± 0.0196 ppm, while vitamin C has a very strong antioxidant activity with an IC50 value of 2.33 ± 0. 1786. Based on this IC50 value, vitamin C is the strongest antioxidant from the ethyl acetate extract of belimbing wuluh leaves, and this leaf extract is classified as a very weak antioxidant.